Effect of tobacco and nicotine on growth of Haemophilus influenzae in vitro. Issue 7 (July 1979) - Roberts, D; Cole, P
Abstract : Two nutritionally poor bacteriological media, prepared from phosphate-buffered saline and from bronchial secretions, support the growth of Haemophilus influenzae only poorly. The presence of tobacco or pure nicotine in these media stimulates the growth of the organism, and the component(s) responsible appear(s) to be volatile.